Springback analysis of torsion of L-sectioned bars of work-hardening materials - Dwivedi J.P.; Upadhyay P.C.; Talukder N.K.D. (My University, 2025)
This paper deals with the torsional springback problems of L-sectioned bars of non-linear work-hardening materials, the properties of which can be modelled by a deformation theory constitutive equation of the Ramberg-Osgood type. The results have been verified experimentally with mild steel bars. It was found that the experimental results agree well with theoretical results obtained numerically. © 1992.